Multifunctional C/ZnS nanocapsules modified carbon cloth as 3D conductive collector and lithium host for stable lithium metal anodes - Zhou, Luo-Ting; Zhang, Qian-Qian; Yuan, Hua-Dong; Fang, Ru-Yi; Luo, Jian-Min; Huang, Hui; Gan, Yong-Ping; Xia, Yang; Zhang, Jun; Xia, Xin-Hui; He, Xin-Ping; Jin, Cheng-Bin; et al. (Rare metals, 2025)
Lithium (Li) metal anodes (LMAs) that employ three-dimensional lithiophilic frameworks are among the most promising options for constructing high-energy-density rechargeable batteries. Herein, hollow ZnS nanosheets with the coating of N-doped carbon are modified on the surface of carbon cloth (NCHZS@CC) to serve as the host material for Li metal. It is revealed that the high surface area of NCHZS@CC can significantly reduce local current density and mitigate volume change during cycling. More importantly, the lithiated product of ZnS, confined within the carbon cage, facilitates the uniform deposition of Li metal on carbon fibers and promotes the formation of a stable solid electrolyte interphase enriched with Li2S, thereby improving long-term performance as the cycling progresses. Consequently, the LMAs based on NCHZS@CC demonstrate an impressive cycle life beyond 560 h with an ultralow overpotential of 38 mV at a current density of 5 mA cm−2 with a capacity of 1 mAh cm−2 in the symmetric cell. In addition, when matched with a high mass loading cathode of LiFePO4 (11.5 mg cm−2), the assembled full cell displays outstanding performance, achieving 900 cycles at a rate of 2C.